The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/iai.00398-13
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptococcal Platelet-Activating Factor Acetylhydrolase Variants That Are Involved in Innate Immune Evasion

Abstract: Human pathogen group A streptococcus (GAS) has developed mechanisms to subvert innate immunity. We recently reported that the secreted esterase produced by serotype M1 GAS (SsE M1 ) reduces neutrophil recruitment by targeting platelet-activating factor (PAF M28 in a covS deletion mutant of GAS increased neutrophil recruitment and reduced skin infection, whereas in trans expression of SsE M28 in GAS reduced neutrophil infiltration and increased skin invasion in subcutaneous infection of mice. These results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…We next checked the SsE expression of the 11 SpeB AϪ variants as an indicator of whether these covRS mutants enhanced expression of virulence genes. SsE solely confers the enzymatic activity of hydrolyzing platelet-activating factor (PAF) in GAS culture supernatants, and the PAF hydrolysis activity increases when the covS gene is deleted or has a null mutation (14,25,36). The PAF hy- Aϩ colonies in the same test.…”
Section: Time Course Of In Vivo Accumulation Of Mgas2221 Spebmentioning
confidence: 81%
“…We next checked the SsE expression of the 11 SpeB AϪ variants as an indicator of whether these covRS mutants enhanced expression of virulence genes. SsE solely confers the enzymatic activity of hydrolyzing platelet-activating factor (PAF) in GAS culture supernatants, and the PAF hydrolysis activity increases when the covS gene is deleted or has a null mutation (14,25,36). The PAF hy- Aϩ colonies in the same test.…”
Section: Time Course Of In Vivo Accumulation Of Mgas2221 Spebmentioning
confidence: 81%
“…The two PCR fragments were fused together in subsequent overlay PCR via the 21-bp complementary sequences that are underlined in primers 2 and 3 using primers 1 and 4. The fused PCR product first was cloned into the donor vector pDONR221 in the BP Clonase reaction and then into pGRV-RFA (29) in the LR Clonase reaction using the Gateway cloning kit. pGRV-RFA was renamed p740-RFA.…”
Section: Methodsmentioning
confidence: 99%
“…SsE is required for the skin invasion by hypervirulent serotype M1 GAS isolates in a mouse model of necrotizing fasciitis (18). The basis for the role of SsE in skin invasion has been proposed to be mediated by SsE inhibition of neutrophil recruitment in GAS skin infections (19,24), and the SsE inhibition of the neutrophil response is partly mediated by SsE-catalyzed hydrolysis of PAF (19). In this study, we first demonstrated that the MGAS5005 derivative that produced an enzymatically inactive SsE S178A mutant protein had the same phenotype as the reported phenotype of an sse deletion mutant of MGAS5005, with a reduction in skin invasion and enhancement in neutrophil recruitment during subcutaneous infection of mice (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…SsE in 40 mM Tris-HCl, pH 8.0, was incubated with 2B11 at various concentrations in wells of a 96-well plate at room temperature for 5 min, and the PAF acetylhydrolase activity of the reaction mixtures was then assayed using a 2-thio-PAF assay as previously described (24). Briefly, the SsE-2B11 solutions were mixed with 30 l of solution containing 0.88 mM 2-thio-PAF and 1.26 mM 5,5=-dithiobis-(2-nitrobenzoic acid) (DTNB).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation